The Colour of Law : Law Is Constituted from the Colour of Right - Gray, Christopher (Les Cahiers de droit, 2008)
This article shows that the doctrinal category “colour of right” opens a valuable entree to law. Despite the limited spread of its statutory mentions, the surface of the colour, jurisprudence shows that in its depth or saturation it is genetically originary : colour is not reducible to other normativity such as morality, and not reducible to other rationality such as utility. Colour of right takes on the hue of marginality, then, as a phenomenon that is not legal, but defines law by standing outside of it ; colour is contrary to fact, and is never asserted in the form of a claim. The result is that the institution of law can increase its intensity autonomously, due to its detachment from sources other than its own appearance.